2017
DOI: 10.1051/matecconf/201710601001
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and adaptability - key elements of end-user participation in living space designing

Abstract: Abstract. An end-user has the main role in the creation of space where spends most of its lifetime (home, workplace). That is why important that a designer (he first) recognizes what requests of the end-user are. In the reference literature and researches that deal with the spatial organisations and designing of living area, the role of an end-user is essential. However, what does the end user participation mean, actually? At what level an enduser makes a final decision? Is it a choice among several alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The idea is that a building, serving its present purpose, can easily be adapted to the changing requirements, conditions and demands of future generations, whereas otherwise it would be completely or partially demolished. [58][59][60][61][62] In this way, a lot of energy and materials can be saved [58]. In DfA, it is thus important that architects learn and understand how buildings tend to change and evolve over time in order to improve their designs to meet the DfA principles [60].…”
Section: Technical Solutionsmentioning
confidence: 99%
“…The idea is that a building, serving its present purpose, can easily be adapted to the changing requirements, conditions and demands of future generations, whereas otherwise it would be completely or partially demolished. [58][59][60][61][62] In this way, a lot of energy and materials can be saved [58]. In DfA, it is thus important that architects learn and understand how buildings tend to change and evolve over time in order to improve their designs to meet the DfA principles [60].…”
Section: Technical Solutionsmentioning
confidence: 99%
“…A considerable amount of research has been done to define and categorise building adaptability, also referred to as flexibility, changeability, or modifiability (Moharram 1980;Leaman and Bordass 2004;Till and Schneider 2005;Gosling et al 2013;Geraedts et al 2017). Research on adaptability also refers to elasticity or extendibility, that is, the possibility to enlarge or shrink a building, or units within a building, over time (Geraedts 2016;Jakšić et al 2017).…”
Section: Earlier Research On Adaptabilitymentioning
confidence: 99%
“…Each layer has its own technical, functional, and economic lifespan and needs to be separated from the others so that one can be replaced without interfering with the other. The layering theories have been used for systematic and systemic approaches to building adaptability (Gosling et al 2013;Jakšić et al 2017). Geraedts et al (2017) have identified no fewer than 44 flexibility performance indicators for building adaptability.…”
Section: Earlier Research On Adaptabilitymentioning
confidence: 99%
“…En Irak la adaptabilidad en viviendas como herramienta de diseño sostenible, Nueva Zelanda y las viviendas flexibles, las viviendas adaptables en Inglaterra, en Austria se plantea que la vivienda es un sistema de actividad, Alemania y la vivienda cambiante, la vivienda como entidad transformable en el tiempo en los Países Bajos, Portugal y las nociones de flexibilidad residencial, etc. (Montaner et al, 2011;Rian, 2011;Mahdinejad y Ehsani Oskouei, 2016;Jakšic ´ et al, 2017;Acharya, 2013;Minami, 2016;Aziz et al, 2020;Grounds, 2012;French, 2016;Estaji, 2017;Agyefi-Mensah, 2013;Kumar Dhar et al, 2013).…”
Section: Resultados Discusión Teórica-bibliográfica Sobre La Flexibilidad En Viviendasunclassified